Results of routine examinations for parasitic infections of humans from laboratory-submitted samples in Gauteng, North West and Mpumalanga Provinces between 2009 and 2010 - Schwan, Ernst Volker (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.